The Mesoderm-Forming Gene brachyury Regulates Ectoderm-Endoderm Demarcation in the Coral Acropora digitifera - Yasuoka, Yuuri; Shinzato, Chuya; Satoh, Noriyuki (Current biology, 2016)
Blastoporal expression of the T-box transcription factor gene brachyury is conserved in most metazoans [1, 2]. Its role in mesoderm formation has been intensively studied in vertebrates [3–6]. However, its fundamental function near the blastopore is poorly understood in other phyla. Cnidarians are basal metazoans that are important for understanding evolution of metazoan body plans [7, 8]. Because they lack mesoderm, they have been used to investigate the evolutionary origins of mesoderm [1, 9–11]. Here, we focus on corals, a primitive clade of cnidarians that diverged from sea anemones ∼500 mya [12]. We developed a microinjection method for coral eggs to examine Brachyury functions during embryogenesis of the scleractinian coral, Acropora digitifera. Because Acropora embryos undergo pharynx formation after the blastopore closes completely [13–15], they are useful to understand Brachyury functions in gastrulation movement and pharynx formation. We show that blastoporal expression of brachyury is directly activated by Wnt/β-catenin signaling in the ectoderm of coral embryos, indicating that the regulatory axis from Wnt/β-catenin signaling to brachyury is highly conserved among eumetazoans. Loss-of-function analysis demonstrated that Brachyury is required for pharynx formation but not for gastrulation movement. Genome-wide transcriptome analysis demonstrated that genes positively regulated by Brachyury are expressed in the ectoderm of Acropora gastrulae, while negatively regulated genes are in endoderm. Therefore, germ layer demarcation around the blastopore appears to be the evolutionarily conserved role of Brachyury during gastrulation. Compared with Brachyury functions in vertebrate mesoderm-ectoderm and mesoderm-endoderm demarcation [4–6], our results suggest that the vertebrate-type mesoderm may have originated from brachyury-expressing ectoderm adjacent to endoderm. [Display omitted] •brachyury is necessary for pharynx formation in coral embryos•Wnt/β-catenin signaling activates brachyury expression in blastoporal ectoderm•Brachyury activates ectodermal genes but represses endodermal genes at the border•Vertebrate mesoderm appears to originate from brachyury-expressing ectoderm Yasuoka et al. carry out the first gene function analysis in corals (diploblasts), which lack mesoderm. They show that brachyury, a key gene of vertebrate mesoderm formation, maintains the ectoderm-endoderm border in coral embryos. Their results highlight the origin of vertebrate mesoderm from brachyury-expressing ectoderm contiguous with endoderm.